(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article analyzes the impact of a basis verb-motivators on the possibility of formation of resultatives, interpreted the concept of «the result of action» and the «ultimate action» is a semantic characterization of the impact categories and forms of productive structures.